1997
DOI: 10.1089/thy.1997.7.277
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Thyroid Remnant/Metastasis Without Stunning: An Ongoing Dilemma

Abstract: The use of 131I doses of several mCi for scans can stun the thyrocytes and thyroid cancer cells, whereas the usual dose (300 microCi) of 123I does not. We compared the diagnostic accuracy of the 123I (300 microCi) scans and that of 131I (3-10 mCi) scans in 155 patients. The diagnostic accuracy of a 123I scan in detecting functioning thyroid remnant/metastasis was 89.5% (77/86 scans) and that of a 131I scan was 92.9% (39/42) in 6 week-postoperative patients (p = 0.750). For radioablation therapy follow-up patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(45 citation statements)
references
References 3 publications
3
39
1
2
Order By: Relevance
“…We found a statistically significant higher successful I-131 ablation rate among patients studied with I-123 WBS compared to those studied with I-131 WBS before radioiodine ablation. Our results were consistent with those reported by Park et al, 1997 (27) who compared the successful ablation rate of functioning thyroid tissue, one year following I-131 therapy administered after diagnostic I-123 WBS in 47 patients and after I-131 WBS in 43 patients. Using the one-year follow-up WBS, without a Tg level, they reported that total ablation was obtained in 72% of patients who received (300 µCi) 11.1 MBq of I-123 as diagnostic dosages before ablation and in 56% of those who received (3-10 mCi) 111-370 MBq of I-131 as diagnostic dosages.…”
Section: Discussionsupporting
confidence: 93%
“…We found a statistically significant higher successful I-131 ablation rate among patients studied with I-123 WBS compared to those studied with I-131 WBS before radioiodine ablation. Our results were consistent with those reported by Park et al, 1997 (27) who compared the successful ablation rate of functioning thyroid tissue, one year following I-131 therapy administered after diagnostic I-123 WBS in 47 patients and after I-131 WBS in 43 patients. Using the one-year follow-up WBS, without a Tg level, they reported that total ablation was obtained in 72% of patients who received (300 µCi) 11.1 MBq of I-123 as diagnostic dosages before ablation and in 56% of those who received (3-10 mCi) 111-370 MBq of I-131 as diagnostic dosages.…”
Section: Discussionsupporting
confidence: 93%
“…This occurs most prominently with higher I-131 activities (5-10 mCi) and with increasing time between the diagnostic dose and therapy. [46][47] Although stunning is not visually appreciated at activities of 1 -3 mCi, the accuracy of low dose scans has been questioned, particularly in patients who have had previous RAI therapy. reasons: 1) optimal I-123 activity and time to scan after I-123 administration is not known; 2) I-123 is expensive and not universally available; 3) the short half-life (t1/2 = 13 hours) of I-123 makes handling this isotope more difficult; 4) stunning may also occur, although to a lesser degree than I-131.…”
Section: D) Is There a Need For Pre-therapy Whole Body Scintigraphy Wmentioning
confidence: 99%
“…Numerous studies have reported that diagnostic exposure to 131 I may diminish subsequent uptake of the therapeutic dose, a phenomenon known as thyroid stunning, which potentially may compromise the therapeutic efficiency and outcome of radioiodine treatment (reviewed in refs. [2][3][4][5]. The stunning mechanism has for long been obscure mainly because of lack of experimental data.…”
Section: Introductionmentioning
confidence: 99%